Assessment of frequency drift on CEST MRI and dynamic correction: application to gagCEST at 7 T. Issue 1 (31st May 2018) - Windschuh, Johannes; Zaiss, Moritz; Ehses, Philipp; Lee, Jae‐Seung; Jerschow, Alexej; Regatte, Ravinder R.
Abstract : Purpose: To investigate the effect of a frequency drift of the static magnetic field on 3D CEST MRI based on glycosaminoglycans (GAGs) of articular cartilage at 7 T and to introduce a retrospective correction method that uses the phase images of the gradient‐echo readout. Methods: Repeated gagCEST and B0 measurements were performed in a glucose model solution and in vivo in the knee joint of 3 healthy volunteers at 7 T. Phase images of the modified 3D rectangular spiral centric–reordered gradient‐echo CEST sequence were used to quantify and compensate the apparent frequency drift in repeated gagCEST measurements. Results: The frequency drift of the MRI scanner strongly influences the gagCEST signal in the articular cartilage of the human knee joint. The gagCEST signal in the articular cartilage is changed by 0.18%/Hz while an average drift of 0.7 ± 0.2 Hz/minute was observed. The proposed correction method can be applied retrospectively without the need of additional measurements and provides improved comparability and reproducibility for gagCEST studies. This correction method may also be of interest for other applications of CEST MRI. Conclusion: Prospective or retrospective correction of the frequency drift of the MRI scanner is essential for reproducible gagCEST measurements. The proposed retrospective correction method fulfills this requirement without the need of additional measurements.